Impure thoughts : Sexuality, Catholicism and literature in twentieth-century Ireland - Cronin, Michael G. (Book collections on Project MUSE., 2018)
Impure Thoughts is the first study of the twentieth-century Irish Catholic bildungsroman. This comparative examination of six Irish novelists tracks the historical evolution of a literary genre and its significant role in Irish culture. With chapters on James Joyce and Kate O'Brien, along with studies of Maura Laverty, Patrick Kavanagh, Edna O'Brien and John McGahern, this book offers a fresh new approach to the study of twentieth-century Irish writing and of the twentieth-century novel. Combining the study of literature and of archival material Impure Thoughts also develops a new interpretive framework for studying the history of sexuality in twentieth-century Ireland. Addressing itself to a wide set of interdisciplinary questions about Irish sexuality, modernity and post-colonial development, as well as Irish literature, it will be of interest to students and scholars in various disciplines, including literary studies, history, sociology and gender studies.